A bio-based furan arylon powder containing a benzimidazole structure and an integrated preparation method and coated separator thereof
Patent Information
- Application Number
- CN202611234096.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-27
AI Technical Summary
然而,上述现有技术仍存在明显不足:其一,产物多为纤维或沉析纤维形态,溶解性能差,配制隔膜涂覆液需配套复杂的溶解工序;其二,材料力学性能与耐热性能仍存在较大提升空间;其三,制备工艺多为间歇式操作,聚合、成型、洗涤、干燥工序相互独立,生产效率低下、能耗较高;其四,工艺多采用N-甲基吡咯烷酮(N-methyl pyrrolidone,NMP)/氯化钙复合溶剂体系,溶剂回收难度大,整体生产成本偏高
(1)生物基来源,绿色可持续:本发明采用生物基呋喃二甲酰氯替代石油基对苯二甲酰氯,以呋喃环替代苯环,降低了对石油资源的依赖,符合绿色低碳发展方向。呋喃环上的氧原子可提升聚合物对电解液的浸润性,进而改善锂离子电池综合性能。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of bio-based polymer materials technology, specifically relating to a bio-based furan aramid powder containing a benzimidazole structure, its integrated preparation method, and a coated diaphragm. Background Technology
[0002] Aromatic polyamides (i.e., aramid fibers) are a class of high-performance synthetic polymer materials composed of aromatic rings and amide bonds. They possess excellent high-temperature resistance, chemical corrosion resistance, and mechanical properties, and are widely used in important fields such as new energy, aerospace, and national defense. Currently, the mainstream aramid fibers on the market mainly include poly(p-phenylenetephthalamide) [PPTA, i.e., para-aramid] and poly(m-phenyleneisophthalamide) [PMIA, i.e., meta-aramid]. The raw materials for the preparation of both types of aramids are derived from petroleum-based fossil resources. The over-exploitation and large-scale use of fossil resources will exacerbate greenhouse gas emissions, and the rigid benzene ring structure in the molecular chain of petroleum-based aramids leads to poor solubility of the material, greatly increasing the difficulty of subsequent processing. Furan compounds are currently the only bio-based platform molecules containing a rigid ring structure. Their structure contains both aromatic rings and oxygen-containing furan rings. The oxygen atoms in the furan ring can effectively enhance the polymer's wettability to electrolytes. Appropriately introducing furan units into the polymer molecular chain can significantly improve the polymer's solubility and processing performance while ensuring the material's heat resistance.
[0003] Existing technologies include studies on the preparation of bio-based aramids using furanyl chloride and m-phenylenediamine as raw materials. Furthermore, Chinese invention patents ZL202110400674.0 and ZL202110399634.9 disclose related technologies for lithium batteries and separator coating solutions based on biomass furan-based polymers. However, these existing technologies still have significant shortcomings: First, the products are mostly in fibrous or precipitated fiber form, with poor solubility, requiring complex dissolution processes to prepare the separator coating solution; second, there is still considerable room for improvement in the mechanical and heat resistance properties of the materials; third, the preparation processes are mostly intermittent operations, with polymerization, molding, washing, and drying processes operating independently, resulting in low production efficiency and high energy consumption; fourth, the processes often use an N-methyl pyrrolidone (NMP) / calcium chloride composite solvent system, which makes solvent recovery difficult and leads to high overall production costs. Summary of the Invention
[0004] To address the above-mentioned problems, this invention discloses a bio-based furan aramid powder containing a benzimidazole structure, its integrated preparation method, and a coated diaphragm.
[0005] The technical solution of the present invention is as follows: First, the present invention provides a bio-based furan aramid powder containing a benzimidazole structure, wherein the molecular chain contains a bio-based furan ring structure and a benzimidazole structure, and the intrinsic viscosity is 1.5~3.5 dL / g.
[0006] This invention organically combines a bio-based furan structure with a benzimidazole structure, and significantly enhances the intermolecular forces by leveraging the heterocyclic conjugation effect and molecular polarity. The resulting material has superior tensile mechanical properties compared to traditional para-aramid fibers, while also possessing excellent characteristics such as lightweight, high strength and high modulus, high heat resistance and solvent resistance. It simultaneously improves the material's solubility and mechanical properties while maintaining excellent heat resistance.
[0007] Preferably, the bio-based furan aramid powder containing benzimidazole structure has a particle size ≤2.0mm, a moisture content ≤5%, and good solubility in polar solvents.
[0008] More preferably, the polar solvent includes at least one of N,N-dimethylacetamide (DMAC), N-methylpyrrolidone (NMP), or N,N-dimethylformamide (DMF).
[0009] Secondly, this invention provides an integrated preparation method for the above-mentioned bio-based furan aramid powder, comprising the following steps: The benzimidazole-containing copolydiamine component was added to N,N-dimethylacetamide / lithium chloride (LiCl) solvent, and after being fully dissolved, bio-based furan dicarboxylic acid chloride was added to carry out a low-temperature solution polycondensation reaction to obtain a benzimidazole-containing bio-based furan heterocyclic aramid polymer solution. A compressed gas-assisted atomization method was used to spray-form a benzimidazole-containing bio-based furan heterocyclic aramid polymer liquid to obtain benzimidazole-structured bio-based furan aramid powder particles. The bio-based furan aramid powder particles containing benzimidazole structure are post-processed by a continuous process integrating centrifugal washing and dehydration, vacuum drying and automatic screening to obtain bio-based furan aramid powder containing benzimidazole structure.
[0010] This invention replaces petroleum-based terephthaloyl chloride with bio-based furanyl chloride and adds a benzimidazole-containing copolydiamine component. The polymer solution is then subjected to low-temperature solution polymerization in an N,N-dimethylacetamide / lithium chloride solvent system to obtain a benzimidazole-containing bio-based furanyl heterocyclic aramid polymer solution. A continuous process integrating centrifugal washing and dehydration, vacuum drying, and automated screening is then used to produce a benzimidazole-containing bio-based furanyl aramid powder with uniform particle size and excellent solubility. This powder is primarily used for coating lithium-ion battery separators. By introducing this benzimidazole structure, this invention significantly improves the mechanical and heat resistance properties of the material while maintaining good solubility of furanyl aramid, achieving a fully integrated continuous production process from polymerization reaction to finished powder product.
[0011] Preferably, the molar ratio of the benzimidazole-containing copolydiamine component, N,N-dimethylacetamide / lithium chloride solvent, and bio-based furanyl chloride is 1:(70~75):(0.95~1.05).
[0012] More preferably, the copolydiamine component containing a benzimidazole structure includes: m-phenylenediamine, p-phenylenediamine, and a diamine monomer containing a benzimidazole structure.
[0013] More preferably, the molar ratio of m-phenylenediamine, p-phenylenediamine and diamine monomer containing benzimidazole structure is (5~10):(2~5):(2~5).
[0014] Particularly preferred is a molar ratio of 2:1:1 for m-phenylenediamine, p-phenylenediamine, and a diamine monomer containing a benzimidazole structure.
[0015] Further preferred, the diamine monomer containing the benzimidazole structure includes at least one of 2-(4-aminophenyl)-5-aminobenzimidazole [2-(4-Aminophenyl)-1H-benzimidazol-5-amine, APBIA] or 5(6)-amino-2-(4-aminophenyl)benzimidazole.
[0016] Preferably, in the N,N-dimethylacetamide / lithium chloride solvent, the mass fraction of lithium chloride is 3% to 8%.
[0017] More preferably, the mass fraction of lithium chloride is 4% to 6%.
[0018] Preferably, the bio-based furanyl chloride includes at least one of 2,3-furanyl chloride, 2,4-furanyl chloride, or 2,5-furanyl chloride.
[0019] Preferably, the bio-based furan heterocyclic aramid polymer solution containing benzimidazole has a dynamic viscosity of 1000~2000 cp.
[0020] More preferably, the bio-based furan heterocyclic aramid polymer solution containing benzimidazole has a dynamic viscosity of 1300~1500 cp.
[0021] More preferably, complete dissolution includes: controlling the system temperature to -10~30°C under inert gas protection.
[0022] Further preferably, the inert gas includes nitrogen or argon.
[0023] Further preferred, the system temperature is controlled at -5~5℃.
[0024] More preferably, the low-temperature solution polycondensation reaction includes controlling the reaction temperature to be -5~60℃ and the reaction time to be 2~5h.
[0025] Further preferred, the reaction temperature is controlled at -5~10℃.
[0026] To synergistically enhance the solubilizing effect of lithium chloride in the N,N-dimethylacetamide / lithium chloride solvent system.
[0027] Preferably, the pH of the benzimidazole-containing bio-based furan heterocyclic aramid polymer solution is 7-8.
[0028] More preferably, after the low-temperature solution polycondensation reaction is completed, a neutralizing agent is added to adjust the pH of the benzimidazole-containing bio-based furan heterocyclic aramid polymer solution to 7-8.
[0029] Further preferred, the neutralizing agent includes lithium hydroxide (LiOH).
[0030] Preferably, lithium hydroxide includes lithium hydroxide monohydrate.
[0031] Preferably, the compressed gas-assisted atomization method includes: the atomizing gun is a pneumatic atomizing gun or an ultrasonic atomizing gun, the atomizing nozzle is made of stainless steel with an orifice diameter of 0.15~0.3mm, the compressed gas is nitrogen or compressed air, and the working pressure is 0.3~0.8MPa.
[0032] More preferably, the orifice diameter of the atomizing nozzle is 0.2 mm.
[0033] More preferably, the working pressure is 0.4~0.6MPa.
[0034] More preferably, the spray direction is perpendicular to the coagulation bath surface, and the spray gun outlet is 20~50cm away from the coagulation bath surface of the water bath.
[0035] Preferably, the centrifugal washing and dehydration includes: the washing liquid is deionized water or a mixture of deionized water and solvent; the number of washing and dehydration treatments is 2 to 5 times; the centrifugation speed is 500 to 3000 rpm; and the time for a single washing and dehydration treatment is 10 to 30 minutes.
[0036] More preferably, the solvent is at least one of N,N-dimethylacetamide, N-methylpyrrolidone, or N,N-dimethylformamide.
[0037] More preferably, centrifugal washing and dehydration are carried out in a centrifuge.
[0038] Further preferred options include centrifuges with a diameter of 1000~1500mm and a capacity of 500~1000L.
[0039] Preferably, vacuum drying includes: vacuum drying the powder after centrifugal washing and dehydration, with a drying temperature of 140~180℃, a vacuum degree of -0.098~-0.08MPa, and a drying time of 2~10h.
[0040] More preferably, the drying temperature is 160°C, the vacuum degree is -0.095MPa, and the drying time is 4~6h.
[0041] More preferably, vacuum drying is carried out in a drum dryer or a double-cone rotary vacuum dryer.
[0042] More preferably, the rotation speed of the drum dryer is 5~30 rpm.
[0043] Preferably, the automatic screening includes: sieving the vacuum-dried powder, wherein the sieve mesh size is 10 mesh.
[0044] More preferably, automatic screening is carried out in an automatic sieving machine with a vibration frequency of 1000~3000 times / min.
[0045] Finally, the present invention provides a coated diaphragm, the preparation method of which is as follows: The above-mentioned bio-based furan aramid powder containing benzimidazole structure was dissolved in an aprotic polar solvent to prepare a coating solution with a mass fraction of 2% to 15%. The coating solution is applied to the surface of a lithium-ion battery separator substrate, and then solidified and dried to obtain the coating.
[0046] The coated diaphragm provided by this invention exhibits significantly improved performance compared to benzimidazole-free bio-based furan heterocyclic aramid coated diaphragms. Specifically, it has a heat shrinkage rate ≤3% at 150℃; a membrane rupture temperature ≥230℃; an electrolyte contact angle ≤25°, significantly superior to traditional polyolefin diaphragms; and an ionic conductivity ≥0.6×10⁻⁶. -4 S / cm; compared with wet-process polyethylene film (160MPa, 320gf), the tensile strength is increased by 15%~30%, and the puncture strength is increased by ≥60%.
[0047] Preferably, the aprotic polar solvent includes at least one of N,N-dimethylacetamide, N-methylpyrrolidone, or N,N-dimethylformamide.
[0048] Preferably, the lithium-ion battery separator substrate includes polyethylene (PE) separator, polypropylene, or polyimide.
[0049] The beneficial effects of this invention are: (1) Bio-based source, green and sustainable: This invention uses bio-based furanyl chloride to replace petroleum-based terephthaloyl chloride, and replaces the benzene ring with the furan ring, which reduces dependence on petroleum resources and is in line with the direction of green and low-carbon development. The oxygen atoms on the furan ring can improve the wettability of the polymer to the electrolyte, thereby improving the overall performance of the lithium-ion battery.
[0050] (2) N,N-Dimethylacetamide / lithium chloride solvent system, environmentally friendly and efficient: This invention uses an N,N-dimethylacetamide / lithium chloride solvent system to replace the traditional N-methylpyrrolidone / calcium chloride system. N,N-dimethylacetamide has lower toxicity and a lower salt content, which is more conducive to solvent recovery and industrial production. Lithium chloride has a small molecular weight, requires less co-solvent, and has lower desalination pressure. At the same time, lithium hydroxide is used as a neutralizing agent. The lithium chloride generated by the neutralization reaction can synergistically play a co-solvent role with the original lithium chloride in the solvent system, avoiding the problems of environmentally unfriendly interface and high disposal cost of calcium chloride caused by calcium hydroxide neutralization.
[0051] (3) The introduction of benzimidazole structure significantly improves mechanical properties: In this invention, a diamine monomer containing benzimidazole structure is introduced into the bio-based furan aramid molecular chain as a third copolymer component, which enhances the intermolecular forces through heterocyclic conjugation effect and polar interaction; the benzimidazole heterocycle can improve the rigidity of the molecular chain and strengthen the hydrogen bonding effect, so that the mechanical tensile strength of the copolymer is significantly higher than that of bio-based furan aramid without the introduction of benzimidazole structure.
[0052] (4) Significantly improved heat resistance: The benzimidazole structure can significantly improve the thermal stability of the polymer. The imidazole ring enhances the inter-chain interaction, making the thermal decomposition temperature and glass transition temperature of the copolymer significantly higher than those of ordinary bio-based furan aramid. The resulting coated diaphragm has a membrane breakage temperature ≥230℃ and a thermal shrinkage rate ≤3% at 150℃.
[0053] (5) Excellent solubility: Although the benzimidazole structure enhances intermolecular forces, the polar oxygen atoms on the furan ring can effectively improve the polymer solubility. This invention, by precisely controlling the copolymer composition and molecular weight (intrinsic viscosity 1.5~3.5 dL / g), enables the copolymer to maintain excellent heat resistance and mechanical properties while still possessing excellent solubility in polar solvents.
[0054] (6) Integrated continuous production with high efficiency: This invention integrates polymerization, spray molding, centrifugal washing and dehydration, vacuum drying and automatic sieving into an integrated continuous production process. The process is seamlessly connected, which reduces material transfer loss and energy consumption in intermittent production, greatly improves production efficiency, and is suitable for large-scale industrial production.
[0055] (7) Atomization molding, unique powder form: The present invention directly atomizes the polymer liquid into particles through atomizing nozzles, which is different from the traditional fiber or precipitated fiber form; the powder product does not require secondary crushing, has uniform particle size (can pass through a 10-mesh sieve), and can be directly prepared into coating liquid for diaphragm coating, which significantly simplifies the coating process.
[0056] (8) Excellent overall performance of the coated membrane: The coated membrane made from the bio-based furan aramid powder containing benzimidazole structure prepared by the powder of this invention exhibits outstanding performance in terms of mechanical strength, thermal shrinkage rate, membrane breakage temperature, electrolyte wettability, ionic conductivity and puncture strength, which can effectively improve the safety and overall electrochemical performance of lithium-ion batteries. Detailed Implementation The specific embodiments listed in this invention are merely examples, and the invention is not limited to the specific embodiments described below. For those skilled in the art, any equivalent modifications and substitutions to the embodiments described below are also within the scope of this invention. Therefore, all equivalent transformations and modifications made without departing from the spirit and scope of this invention should be covered within its scope. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. All reagents or instruments whose manufacturers are not specified are commercially available conventional products. To better illustrate this invention, numerous specific details are provided in the following detailed embodiments. Those skilled in the art should understand that this invention can be practiced even without certain specific details. In other embodiments, methods, means, equipment, and steps well known to those skilled in the art are not described in detail in order to highlight the main points of this invention.
[0057] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as commonly understood by one of ordinary skill in the art. Unless otherwise specified, all units used in this specification are International Standard Units (SI), and all numerical values and ranges appearing in this invention should be understood to include systematic errors unavoidable in industrial production.
[0058] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0059] Example 1 This embodiment provides a bio-based furan aramid powder containing a benzimidazole structure, and its integrated preparation method is as follows: Low-temperature solution polymerization: A diamine monomer containing a benzimidazole structure is added to an N,N-dimethylacetamide / lithium chloride solvent. After complete dissolution, 2,5-furandicarboxylic acid chloride is added, and a low-temperature solution polycondensation reaction is carried out to obtain a bio-based furan heterocyclic aramid polymer solution containing benzimidazole.
[0060] Specifically, in a polymerization reactor equipped with a stirrer, thermometer, and nitrogen inlet, 10000g of N,N-dimethylacetamide and 850g of lithium chloride (7.8% by mass) were added and stirred until completely dissolved. Then, 0.75mol of m-phenylenediamine, 0.375mol of p-phenylenediamine, and 0.375mol of 2-(4-aminophenyl)-5-aminobenzimidazole were added and stirred until completely dissolved under nitrogen protection, with the system temperature controlled at -5℃. Next, 1.5mol of 2,5-furandicarboxylic acid chloride was added in batches, maintaining the reaction temperature at -5℃ for 5 hours. After the reaction, lithium hydroxide powder was added to adjust the pH to 7.6, yielding a benzimidazole-containing bio-based furan heterocyclic aramid polymer solution. The dynamic viscosity of the above polymer solution was tested to be 1380 cp.
[0061] Spray molding: The obtained polymer liquid is sprayed using compressed gas-assisted atomization. The atomizing gun is a pneumatic atomizing gun with a 0.2mm orifice stainless steel nozzle. The compressed gas is nitrogen with a working pressure of 0.5MPa. The spray direction is perpendicular to the coagulation bath surface. The nozzle outlet is 20cm away from the coagulation bath surface. After atomization, the polymer liquid enters the coagulation bath and solidifies to obtain bio-based furan aramid powder particles containing benzimidazole structure.
[0062] Post-processing: The bio-based furan aramid powder particles containing benzimidazole structure are post-processed by a continuous process integrating centrifugal washing and dehydration, vacuum drying and automatic screening to obtain bio-based furan aramid powder containing benzimidazole structure.
[0063] Specifically, centrifugal washing and dehydration: The powder particles obtained above are washed and dehydrated in a centrifuge. The washing liquid is deionized water. The centrifuge has a diameter of 1000 mm and a capacity of 500 L. The washing and dehydration processes are repeated 3 times each. The centrifugation speed is 2500 rpm and the time for each washing and dehydration process is 10 min.
[0064] Vacuum drying: The powder after centrifugal washing and dehydration is fed into a double cone rotary vacuum dryer and dried for 5 hours at 160℃ and a vacuum of -0.095MPa, with the drum speed at 15rpm.
[0065] Automatic sieving: The vacuum-dried powder is sieved through a 10-mesh (approximately 2.0 mm aperture) automatic sieve. The vibration frequency of the automatic sieve is 2000 times / min, resulting in bio-based furan aramid powder containing a benzimidazole structure.
[0066] According to the test results, the intrinsic viscosity of the bio-based furan aramid powder obtained in this embodiment is 2.35 dL / g, the powder particle size is ≤2.0 mm, and the moisture content is 2.3%.
[0067] Application Example 1 This application example provides a coated diaphragm, the preparation method of which is as follows: The bio-based furan aramid powder containing benzimidazole structure obtained in Example 1 was dissolved in N,N-dimethylacetamide to prepare a coating solution with a mass fraction of 5%. The dissolution time was 15 min. The coating solution was uniform and transparent. After coating it onto the surface of a polyethylene membrane, it was solidified and dried to obtain a coated membrane containing bio-based furan aramid powder containing benzimidazole structure.
[0068] Tests showed that the above-mentioned diaphragm had a heat shrinkage rate of 2.5% at 150℃; a membrane rupture temperature of 235℃; an electrolyte contact angle of 22°, significantly better than that of traditional polyolefin diaphragms; and an ionic conductivity of 0.65 × 10⁻⁶. -4 S / cm; compared to wet-process polyethylene film, tensile strength is increased by 22% and puncture strength is increased by 65%.
[0069] Example 2 This embodiment provides a bio-based furan aramid powder containing a benzimidazole structure, and its integrated preparation method is as follows: Low-temperature solution polymerization: A benzimidazole-containing diamine monomer was added to an N,N-dimethylacetamide / lithium chloride solvent and fully dissolved. Then, 2,3-furandicarboxylic acid chloride was added, and a low-temperature solution polycondensation reaction was carried out to obtain a benzimidazole-containing bio-based furan heterocyclic aramid polymer solution. The system temperature was controlled at 5℃, the reaction temperature at 10℃, and the reaction time at 2h. The mass percentage of lithium chloride was 5.7%. The benzimidazole-containing diamine monomer consisted of m-phenylenediamine, p-phenylenediamine, and 5(6)-amino-2-(4-aminophenyl)benzimidazole, with a molar ratio of 10:2:5. The dynamic viscosity of the above polymer solution was tested to be 1480 cp.
[0070] Spray molding: The obtained polymer liquid is sprayed using compressed gas-assisted atomization. The atomizing gun is a pneumatic atomizing gun with a 0.3mm orifice stainless steel nozzle. The compressed gas is nitrogen with a working pressure of 0.6MPa. The spray direction is perpendicular to the coagulation bath surface. The nozzle outlet is 50cm away from the coagulation bath surface. After atomization, the polymer liquid enters the coagulation bath and solidifies to obtain bio-based furan aramid powder particles containing benzimidazole structure.
[0071] The post-processing steps are the same as in Example 1, and are omitted here, to obtain a bio-based furan aramid powder containing a benzimidazole structure.
[0072] According to the test results, the intrinsic viscosity of the bio-based furan aramid powder obtained in this embodiment is 3.21 dL / g, the powder particle size is ≤2.0 mm, and the moisture content is 1.5%.
[0073] Application Example 2 This application example provides a coated diaphragm, the preparation method of which is as follows: The bio-based furan aramid powder containing benzimidazole structure obtained in Example 2 was dissolved in N,N-dimethylacetamide to prepare a coating solution with a mass fraction of 5%. The dissolution time was 15 min. The coating solution was uniform and transparent. After coating it onto the surface of a polyethylene membrane, it was solidified and dried to obtain a coated membrane containing bio-based furan aramid powder containing benzimidazole structure.
[0074] Tests showed that the above-mentioned diaphragm had a heat shrinkage rate of 1.8% at 150℃; a membrane rupture temperature of 233℃; an electrolyte contact angle of 24°, significantly better than that of traditional polyolefin diaphragms; and an ionic conductivity of 0.62 × 10⁻⁶. -4 S / cm; compared to wet-process polyethylene film, tensile strength is increased by 28% and puncture strength is increased by 62%.
[0075] Example 3 This embodiment provides a bio-based furan aramid powder containing a benzimidazole structure, and its integrated preparation method is as follows: Low-temperature solution polymerization: A diamine monomer containing a benzimidazole structure was added to an N,N-dimethylacetamide / lithium chloride solvent and, after complete dissolution, 2,4-furandicarboxylic acid chloride was added, followed by a low-temperature solution polycondensation reaction to obtain a bio-based furan heterocyclic aramid polymer solution containing benzimidazole. The lithium chloride content was 4.4% by mass, and the benzimidazole structure consisted of m-phenylenediamine, p-phenylenediamine, and 2-(4-aminophenyl)-5-aminobenzimidazole in a molar ratio of 10:5:2. The dynamic viscosity of the polymer solution was measured to be 1690 cp.
[0076] Spray molding: The obtained polymer liquid is sprayed using compressed gas-assisted atomization. The atomizing gun is a pneumatic atomizing gun with a 0.15mm orifice stainless steel nozzle. The compressed gas is nitrogen with a working pressure of 0.4MPa. The spray direction is perpendicular to the coagulation bath surface, and the nozzle outlet is 15cm away from the coagulation bath surface. After atomization, the polymer liquid enters the coagulation bath and solidifies to obtain bio-based furan aramid powder particles containing benzimidazole structure.
[0077] The post-processing steps are the same as in Example 1, and are omitted here, to obtain a bio-based furan aramid powder containing a benzimidazole structure.
[0078] According to the test results, the intrinsic viscosity of the bio-based furan aramid powder obtained in this embodiment is 1.99 dL / g, the powder particle size is ≤2.0 mm, and the moisture content is 1.4%.
[0079] Application Example 3 This application example provides a coated diaphragm, the preparation method of which is as follows: The bio-based furan aramid powder containing benzimidazole structure obtained in Example 3 was dissolved in N,N-dimethylacetamide to prepare a coating solution with a mass fraction of 5%. The dissolution time was 15 min. The coating solution was uniform and transparent. After coating it onto the surface of a polyethylene membrane, it was solidified and dried to obtain a coated membrane containing bio-based furan aramid powder containing benzimidazole structure.
[0080] Tests showed that the above-mentioned diaphragm had a heat shrinkage rate of 2.9% at 150℃; a rupture temperature of 233℃; an electrolyte contact angle of 18°, significantly better than that of traditional polyolefin diaphragms; and an ionic conductivity of 0.6 × 10⁻⁶. -4 S / cm; compared to wet-process polyethylene film, tensile strength is increased by 16% and puncture strength is increased by 61%.
[0081] Example 4 This embodiment provides a bio-based furan aramid powder containing a benzimidazole structure, and its integrated preparation method is as follows: Low-temperature solution polymerization: A benzimidazole-containing diamine monomer was added to an N,N-dimethylacetamide / lithium chloride solvent and, after complete dissolution, 2,5-furandicarboxylic acid chloride was added, followed by a low-temperature solution polycondensation reaction to obtain a benzimidazole-containing bio-based furan heterocyclic aramid polymer solution. The lithium chloride content was 4.4% by mass, and the benzimidazole-containing diamine monomer consisted of m-phenylenediamine, p-phenylenediamine, and 2-(4-aminophenyl)-5-aminobenzimidazole in a molar ratio of 5:2:5. The dynamic viscosity of the polymer solution was measured to be 1595 cp.
[0082] The spray molding and post-processing steps are the same as in Example 1, and are omitted here, to obtain a bio-based furan aramid powder containing a benzimidazole structure.
[0083] According to the test results, the intrinsic viscosity of the bio-based furan aramid powder obtained in this embodiment is 2.88 dL / g, the powder particle size is ≤2.0 mm, and the moisture content is 1.1%.
[0084] Application Example 4 This application example provides a coated diaphragm, the preparation method of which is as follows: The bio-based furan aramid powder containing benzimidazole structure obtained in Example 4 was dissolved in N,N-dimethylacetamide to prepare a coating solution with a mass fraction of 5%. The dissolution time was 15 min. The coating solution was uniform and transparent. After coating it onto the surface of a polyethylene membrane, it was solidified and dried to obtain a coated membrane containing bio-based furan aramid powder containing benzimidazole structure.
[0085] Tests showed that the above-mentioned diaphragm had a heat shrinkage rate of 1.7% at 150℃; a membrane rupture temperature of 239℃; an electrolyte contact angle of 20°, significantly better than that of traditional polyolefin diaphragms; and an ionic conductivity of 0.61×10⁻⁶. -4 S / cm; compared to wet-process polyethylene film, tensile strength is increased by 29% and puncture strength is increased by 62%.
[0086] Comparative Example 1 The difference between this comparative example and Example 1 is that 2-(4-aminophenyl)-5-aminobenzimidazole is not added to the diamine monomer; that is, the diamine monomer is composed of m-phenylenediamine and p-phenylenediamine in a molar ratio of 8:2. The other conditions are the same as in Example 1.
[0087] Tests showed that the coating membrane of the bio-based furan aramid powder obtained in this embodiment had a heat shrinkage rate of 3.5% at 150°C and a tensile strength significantly lower than that of Examples 1-3, indicating that the introduction of the benzimidazole structure has a significant effect on improving heat resistance and mechanical properties.
[0088] Comparative Example 2 The difference between this comparative example and Example 1 is that the post-processing steps lack the centrifugal washing and dehydration step; instead, the bio-based furan aramid powder particles obtained after atomization spray gun molding are directly vacuum dried.
[0089] Tests showed that the bio-based furan aramid powder obtained in this comparative example had high levels of residual solvents and salts; when a 5% coating solution was prepared, its dissolution time in N,N-dimethylacetamide was as long as 90 minutes, and there were insoluble particles in the coating solution, resulting in poor uniformity of the coated membrane surface.
[0090] Comparative Example 3 The difference between this comparative example and Example 1 is that in the post-processing step, the drying is carried out using a regular hot air drying oven (non-vacuum) at a temperature of 160°C.
[0091] Tests showed that the moisture content of the bio-based furan aramid powder obtained in this comparative example was 6.5%; when a 5% coating solution was prepared, its dissolution time in N,N-dimethylacetamide was ≥60 min, and the coating effect was significantly lower than that in Example 1.
[0092] Comparative Example 4 The difference between this comparative example and Example 1 is that: the addition of 10000g N,N-dimethylacetamide was adjusted to 9000g, the addition of 850g lithium chloride was adjusted to 760g, and the addition of 1.5mol 2,5-furandicarboxylic acid in batches was adjusted to 1.65mol 2,5-furandicarboxylic acid in batches.
[0093] The intrinsic viscosity of the bio-based furan aramid powder obtained in this comparative example was 4.20 dL / g. When a 5% coating solution was prepared, its dissolution time in N,N-dimethylacetamide was 125 min. Some powder could not be completely dissolved, and there were obvious gel particles in the coating solution, which could not form a uniform coating layer.
[0094] Comparative Example 5 The difference between this comparative example and Example 1 is that N,N-dimethylacetamide is replaced with N-methylpyrrolidone; lithium chloride is replaced with calcium chloride; and lithium hydroxide is replaced with calcium hydroxide.
[0095] Testing revealed that the dynamic viscosity of the polymerization solution obtained in this comparative example was 2050 cp, significantly increasing the difficulty of solvent recovery. The environmental disposal costs for the neutralization product, calcium chloride, were also high, resulting in an overall production cost higher than in Example 1. When a 5% coating solution was prepared, its dissolution time in N,N-dimethylacetamide was 50 minutes, and the uniformity of the coating solution was slightly lower than in Example 1.
[0096] Comparative Example 6 The difference between this comparative example and Example 1 is that the amount of lithium chloride added is replaced from 850g to 300g, that is, the mass percentage of lithium chloride is 2.9%.
[0097] The dynamic viscosity of the polymerization solution obtained in this comparative example was 9850 cp, the intrinsic viscosity of the resulting bio-based furan aramid powder was 4.82 dL / g, the powder particle size was ≤2.0 mm, and the moisture content was 5.5%. When a 5% coating solution was prepared, some powder could not be completely dissolved, and obvious gel particles were present in the coating solution, making it impossible to form a uniform coating layer.
[0098] Comparative Example 7 The difference between this comparative example and Example 1 is as follows: (1) Adjust the mass of N,N-dimethylacetamide from 10000g to 11500g; (2) When spray molding, adjust the nozzle orifice diameter from 0.2mm to 0.4mm; adjust the working pressure of compressed gas from 0.5MPa to 0.8MPa; adjust the distance between the spray gun outlet and the coagulation bath liquid surface of the machine water bath from 20cm to 60cm.
[0099] Tests showed that the dynamic viscosity of the polymer solution obtained in this comparative example was 1360 cp, the proportion of the obtained bio-based furan aramid powder with a particle size ≥2.0 mm was 75%, the moisture content was 7.5%, and when a 5% coating solution was prepared, some powder could not be completely dissolved, and there were obvious gel particles in the coating solution, which could not form a uniform coating layer.
[0100] The embodiments described above merely illustrate specific implementation methods of this application, and while the descriptions are detailed and specific, they should not be construed as limiting the scope of protection of this application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the technical solution of this application, and these modifications and improvements all fall within the scope of protection of this application.
Claims
1. A bio-based furan aramid powder containing a benzimidazole structure, characterized in that, Its molecular chain contains a bio-based furan ring structure and a benzimidazole structure, and its intrinsic viscosity is 1.5~3.5 dL / g.
2. The bio-based furan aramid powder containing a benzimidazole structure according to claim 1, characterized in that, The bio-based furan aramid powder containing a benzimidazole structure has a particle size ≤2.0mm, a moisture content ≤5%, and good solubility in polar solvents.
3. An integrated preparation method for bio-based furan aramid powder containing a benzimidazole structure as described in any one of claims 1-2, characterized in that it includes the following steps: The benzimidazole-containing copolydiamine component was added to N,N-dimethylacetamide / lithium chloride solvent, and after being fully dissolved, bio-based furan dicarboxylic acid chloride was added to carry out a low-temperature solution polycondensation reaction to obtain a bio-based furan aramid polymer solution containing a benzimidazole structure. The bio-based furan aramid polymer liquid containing a benzimidazole structure was spray-molded using compressed gas-assisted atomization to obtain bio-based furan aramid powder particles containing a benzimidazole structure. The bio-based furan aramid powder particles containing benzimidazole structure are post-processed by a continuous process integrating centrifugal washing and dehydration, vacuum drying and automatic screening to obtain bio-based furan aramid powder containing benzimidazole structure.
4. The integrated preparation method of bio-based furan aramid powder containing a benzimidazole structure according to claim 3, characterized in that, The molar ratio of the benzimidazole-containing copolydiamine component, the N,N-dimethylacetamide / lithium chloride solvent, and the bio-based furanyl chloride is 1:(70~75):(0.95~1.05).
5. The integrated preparation method of bio-based furan aramid powder containing a benzimidazole structure according to claim 4, characterized in that, The benzimidazole-containing copolydiamine component includes: m-phenylenediamine, p-phenylenediamine and benzimidazole-containing diamine monomer, with a molar ratio of (5~10):(2~5):(2~5).
6. The integrated preparation method of bio-based furan aramid powder containing a benzimidazole structure according to claim 5, characterized in that, The diamine monomer containing the benzimidazole structure includes at least one of 2-(4-aminophenyl)-5-aminobenzimidazole or 5(6)-amino-2-(4-aminophenyl)benzimidazole.
7. The integrated preparation method of bio-based furan aramid powder containing a benzimidazole structure according to claim 3, characterized in that, In the N,N-dimethylacetamide / lithium chloride solvent, the mass fraction of lithium chloride is 3%~8%.
8. The integrated preparation method of bio-based furan aramid powder containing a benzimidazole structure according to claim 3, characterized in that, The bio-based furan heterocyclic aramid polymer liquid containing benzimidazole has a dynamic viscosity of 1000~2000 cp.
9. The integrated preparation method of bio-based furan aramid powder containing a benzimidazole structure according to claim 3, characterized in that, The bio-based furanyl chloride includes at least one of 2,3-furanyl chloride, 2,4-furanyl chloride, or 2,5-furanyl chloride.
10. A coated diaphragm, characterized in that, The preparation method is as follows: The bio-based furan aramid powder containing a benzimidazole structure as described in any one of claims 1-2 is dissolved in an aprotic polar solvent to prepare a coating solution with a mass fraction of 2% to 15%. The coating liquid is applied to the surface of a lithium-ion battery separator substrate, and then solidified and dried to obtain the coating.
Citation Information
Patent Citations
Bio-based diaphragm coating liquid, preparation method thereof and application of bio-based diaphragm coating liquid in lithium battery
CN113136121A
Lithium battery diaphragm based on biomass furyl polymer and preparation method of lithium battery diaphragm
CN113140867A